2014
DOI: 10.1007/s00005-014-0318-6
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Receptor Radionuclide Therapy of Differentiated Thyroid Cancer: Efficacy and Toxicity

Abstract: In rare cases of differentiated thyroid carcinoma (DTC), radioiodine treatment is no longer effective due to cell dedifferentiation. Targeting somatostatin receptors in DTC cells by radiolabelled somatostatin analogues could provide an alternative therapy option. The aim of this study was to evaluate safety and efficacy of peptide receptor radionuclide therapy (PRRT) in patients with advanced, non-iodine avid DTC. Eleven patients aged 47–81 years (median: 65 years) with a history of several courses of radioiod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
0
18
0
1
Order By: Relevance
“…In another phase 2 study of 52 patients including 45 with RAIR DTC and 6 with MTC, an ORR of 35% (95% CI 22–49) was reported with axitinib, with a median duration of response of 17 m (95% CI 14–26) [35]. A phase 2 study of 37 patients with RAIR DTC treated with pazopanib demonstrated an ORR of 49% (95% CI 35–68), which were all PRs with a median PFS of 11.7 m (1 to > 23 m) [32], and an additional phase 2 trial is pending (NCT01813136) [138]. Pazopanib has also been studied in 35 patients with MTC, demonstrating a PR rate of 14% (90% CI 5.8–28), with a median PFS of 9.4 m [36].…”
Section: Other Tkis Studied In Thyroid Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In another phase 2 study of 52 patients including 45 with RAIR DTC and 6 with MTC, an ORR of 35% (95% CI 22–49) was reported with axitinib, with a median duration of response of 17 m (95% CI 14–26) [35]. A phase 2 study of 37 patients with RAIR DTC treated with pazopanib demonstrated an ORR of 49% (95% CI 35–68), which were all PRs with a median PFS of 11.7 m (1 to > 23 m) [32], and an additional phase 2 trial is pending (NCT01813136) [138]. Pazopanib has also been studied in 35 patients with MTC, demonstrating a PR rate of 14% (90% CI 5.8–28), with a median PFS of 9.4 m [36].…”
Section: Other Tkis Studied In Thyroid Cancermentioning
confidence: 99%
“…Finally, a number of other exciting agents with various mechanisms of action are undergoing earlier-phase translational study, including other MAPK-pathway inhibitors, additional TKIs, histone deacetylase inhibitors, PPAR-γ-directed agents, proteosome inhibitors, immunotherapy strategies, farnesyl transferase inhibitors, somatostatin receptor radionuclide therapy, and gene therapy techniques. To date, no randomized controlled clinical evidence exists to support their use in thyroid cancer, but a role for these agents may develop as additional data becomes available [10,11,80,82,85,108–118,119138]. …”
Section: Additional Targets and Strategies In Late-stage Developmentmentioning
confidence: 99%
“…Demonstration of somatostatin receptor expression by the means of SRS is a crucial criterion to qualify to such an experimental treatment. The results of PRRT in DTC in our center have been published elsewhere [49]. PRRT was generally well-tolerated but the outcome was rather poor in majority of cases of radioiodine-refractory DTC.…”
Section: Discussionmentioning
confidence: 87%
“…Scenario 1: 177 Lu-DOTATATE Treatment for Documented SSTR-Expressing RAI-Refractory Thyroid Cancer (Score 4 -May Be Appropriate). PRRT with radiolabeled somatostatin analogs has shown promise for the treatment of RAI-refractory metastatic DTC with a demonstrated objective response rate of 27%-60% tumor reduction, as determined by radiologic measurements following RECIST (143,144).…”
Section: Clinical Scenarios and Auc Scoresmentioning
confidence: 99%